General and specific combining ability for quantitative characters in castor (Ricinus communis L.) - K.P. Patel; M.P. Patel; N.R. Joshi and; J.A. Patel (Electronic Journal of Plant Breeding, 2017)
The experimental material consisted of ten monoecious lines, their 45 F1S developed through diallel mating excluding reciprocals, which was evaluated in Randomized Complete Block Design with three replications. The analysis of variance for combining ability revealed that mean square values due to both GCA and SCA and were significant, accordingly the estimates of both σ2GCA and σ2SCA were also significant for all the characters indicating an importance of both additive and non-additive gene effects for the inheritance of studied characters. However, values of potence ratio and predictability ratio revealed preponderance of additive genetic variance for all the characters. Parents ANDCI 10-12, ANDCI 8, ANDCI 10-4 and ANDCI 10-3 were good general combiners for seed yield per plant and other yield contributing characters. The hybrids ANDCI 10-1 x ANDCI 9, ANDCI10-11 x ANDCI 10-12 and ANDCI 8 x ANDCI 10-11,had high per se performance, high heterotic effects and desired sca effects for seed yield per plant and its component characters.